Childhood Arthritis and Rheumatology Research for Dreams Come True Remission - Syuji Takei (MDPI AG, 2022)
In recent years, newly developed therapeutic agents have brought clinical, structural, and functional remission to many pediatric patients with rheumatic diseases that were refractory to conventional therapy. However, achieving these remissions alone is insufficient as a treatment goal, especially for adolescent patients, because advanced therapies have not always encouraged their psychosocial stability and mental maturity. Consequently, various problems have arisen during the puberty and transition period from pediatrics to adult medical care. "Dreams come true remission" is a state of remission that allows patients to have clear dreams for the future in childhood and to increase the potential that their dreams will be realized in adulthood. This new treatment goal may empower children with chronic diseases such as PRDs to overcome the problems occurred during puberty and transition period.